Endogenous biosynthesis of n-3 long-chain PUFA in Atlantic salmon - Mock, Thomas S; Francis, David S; Jago, Matthew K; Glencross, Brett D; Smullen, Richard P; Turchini, Giovanni M (British Journal of Nutrition, 2019)
A more efficient utilisation of marine derived sources of dietary omega-3 long-chain polyunsaturated fatty acids (n-3 LC PUFA) in cultured Atlantic salmon could, amongst other strategies, be facilitated by nutritional strategies that maximise endogenous n-3 LC PUFA synthesis. The objective of the current study was to quantify the extent of n-3 LC PUFA biosynthesis and the resultant effect on fillet nutritional quality in large, market size Atlantic salmon. Four diets were manufactured providing altered levels of dietary omega-3 substrate, namely 18:3n-3, and end-products, namely, 20:5n-3 and 22:6n-3. After 283 days of feeding, fish grew to in excess of 3000g and no differences in growth performance or biometrical parameters were recorded. An analysis of fatty acid composition and in vivo metabolism revealed that post-smolt Atlantic salmon have the potential to endogenously produce n-3 LC PUFA when provided with a substantial amount of dietary omega-3 substrate. Moreover, the extent of endogenous production resulted in fillet levels of n-3 LC PUFA comparable to fish fed a diet with added fish oil. Another major finding was that the presence of abundant dietary omega-3 substrate with the addition of dietary omega-3 end-product (i.e. fish oil) had a positive effect on final fillet levels of n-3 LC PUFA. This was likely the result of the preferential β-oxidation of dietary C18 n-3 PUFA resulting in an apparent conservation of n-3 LC PUFA from catabolism. Ultimately, this study highlights the potential for endogenous synthesis of n-3 LC PUFA to, at least partially, support a substantial reduction, in the amount of dietary fish oil in diets for market sized Atlantic salmon reared in seawater.